Runaway pony - Earhart, Kristin (Marguerite Henry's Misty Inn, 2015)
"A lost pony is cause for a nighttime adventure on Chincoteague Island in this third book of a chapter book series inspired by Marguerite Henry's Misty of Chincoteague. Full Moon Fancy, Fancy for short, is a pony with a knack for getting loose. First she just tramples a herb garden, then she knocks over a wall of a chicken coop, so the hens end up all over the yard and down on the beach. When she gets out one too many times, Willa and Ben are worried shes lost. They set out to track her down in the moonlight! Will they find the runaway pony, or is Fancy lost for good?"